Pelatihan Digital Entrepreneurship bagi Siswa SMK dalam Menghadapi Era Ekonomi Kreatif - Muhammad Ariffin; Uray Andrey Indra Maulana (Dianmas Bhakti: Jurnal Pengabdian pada Masyarakat, 2026)
This community service program aims to enhance the digital entrepreneurship competencies of students at SMK Koperasi Pontianak in facing the creative economy era. The rapid development of digital technology has created new business opportunities, requiring students to possess entrepreneurial skills supported by digital literacy. However, many students at SMK Koperasi Pontianak still lack understanding and practical skills in digital-based entrepreneurship. This program employed a participatory and experiential learning approach through training, practice, and mentoring activities. The implementation stages included preparation, training delivery, assistance, and evaluation using pre-test and post-test methods. The results showed a significant improvement in students’ knowledge, skills, and entrepreneurial intentions. Students were able to create digital business accounts, develop promotional content, and simulate online marketing activities. Furthermore, the program successfully shifted students’ mindset from job seekers to job creators. Despite some limitations, such as internet access and varying levels of digital literacy, the program was effectively implemented. Therefore, this training model has strong potential to be sustainably applied in vocational education to support the development of creative and independent young entrepreneurs